Effects of Fluoxetine on Outcomes at 12 Months After Acute Stroke: Results From EFFECTS, a Randomized Controlled Trial. Issue 10 (1st September 2021) - Lundström, Erik; Isaksson, Eva; Greilert Norin, Nina; Näsman, Per; Wester, Per; Mårtensson, Björn; Norrving, Bo; Wallén, Håkan; Borg, Jörgen; Hankey, Graeme J.; Hackett, Maree L.; Mead, Gillian E.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: The EFFECTS (Efficacy of Fluoxetine—a Randomised Controlled Trial in Stroke) recently reported that 20 mg fluoxetine once daily for 6 months after acute stroke did not improve functional outcome but reduced depression and increased fractures and hyponatremia at 6 months. The purpose of this predefined secondary analysis was to identify if any effects of fluoxetine were maintained or delayed over 12 months. Methods: EFFECTS was an investigator-led, randomized, placebo-controlled, double-blind, parallel group trial in Sweden that enrolled adult patients with stroke. Patients were randomized to 20 mg oral fluoxetine or matching placebo for 6 months and followed for another 6 months. The primary outcome was functional outcome (modified Rankin Scale), at 6 months. Predefined secondary outcomes for these analyses included the modified Rankin Scale, health status, quality of life, fatigue, mood, and depression at 12 months. Results: One thousand five hundred patients were recruited from 35 centers in Sweden between 2014 and 2019; 750 were allocated fluoxetine and 750 placebo. At 12 months, modified Rankin Scale data were available in 715 (95%) patients allocated fluoxetine and 712 (95%) placebo. The distribution of modified Rankin Scale categories was similar in the 2 groups (adjusted common odds ratio, 0.92 [95% CI, 0.76–1.10]). Patients allocated fluoxetine scored worse on memory with a median value of 89 (interquartile range, 75–100) versus 93 (interquartile range, 82–100); P =0.0021 and communication 93 (interquartile range, 82–100) versus 96 (interquartile range, 86–100); P =0.024 domains of the Stroke Impact Scale compared with placebo. There were no other differences in secondary outcomes. Conclusions: Fluoxetine after acute stroke had no effect on functional outcome at 12 months. Patients allocated fluoxetine scored worse on memory and communication on the Stroke Impact Scale compared with placebo, but this is likely to be due to chance. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02683213.